Gulo Pallas 1780 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Gulo Pallas 1780 Gulo Pallas 1780, Spicil. Zool., 14: 25. Type Species: Gulo sibiricus Pallas 1780 Synonyms:. Species and subspecies: 1 species with 6 subspecies: Species Gulo gulo (Linnaeus 1758) Subspecies Gulo gulo subsp. gulo Linnaeus 1758 Subspecies Gulo gulo subsp. albus (Kerr 1702) Subspecies Gulo gulo subsp. katschemakensis Matschie 1918 Subspecies Gulo gulo subsp. luscus Linnaeus 1758 Subspecies Gulo gulo subsp. luteus Elliot 1904 Subspecies Gulo gulo subsp. vancouverensis Goldman 1935 Discussion: Corbet (1978) attributed Gulo to Storr (1780). Gulo Frisch, 1775, is invalid (International Commission on Zoological Nomenclature, 1954 b ). Placed in subfamily Guloninae according to McKenna and Bell (1997). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Carnivora, pp. 532-628 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 607, DOI: 10.5281/zenodo.7316519